BIAS DARI PENGGUNAAN DATA DI MBAR - Jogiyanto Hartono (Journal of Indonesian Economy and Business (JIEB), 1998)
This paper discusses several biases due to the use of data in MBAR (Market Based Accounting Research). They are biases because of non-normality of the data, cross-dependency of the data and non-synchronous trading. This paper identifies conditions of the biases and also provides solutions to overcome the biases.